Avaliação física de um latossolo vermelho textura média, Influenciada pela aplicação de dejetos de suínos e cama aviária - Lima, Leomar Paulo de (2007)
Hog production and poultry raising constitute types of livestock activities which are of paramount social and economic importance for human nutrition in Brazil and also for generating wealth to the country economy through exports. The impressive increase in Brazilian exportation of swine and poultry has lead to intensive raising, that in turn has generated a great amount of manure which must have a viable destination, for without proper treatment may cause serious environmental effects and affect human health. Such residues, due to their high contents of nutrients and organic matter, and for being available in the rural properties at low costs may be utilized by the producers in the fertilization of commercial crops and in the physical recuperation of degraded soils. The objective of this research was to evaluate the influence of the application of swine manure and poultry bed on the recovery of physical properties of a Red Latosol. Two field trials were conducted simultaneously in a typical medium texture dystrophic Red Latosol, under degraded pasture of Brachiaria decumbens sp, located in Uberlândia, Triangulo Mineiro, Minas Gerais. In each experiment the 10x25 m plots received treatments with swine manure in the following amounts: D0 = nihil; D1 = 79.37 m3 ha-1; D2 = 158.73 m3 ha-1; D3 = 238.10 m3 ha-1; D4 = 317.46 m3 ha-1 and the treatments with poultry bed in the following amounts: D0 = nihil; D1 = 1,737 kg ha-1; D2 = 3,473 kg ha- 1; D3 = 5, 209 kg ha-1; D4 = 6,945 kg ha-1. The application of the residues were carried out in November 2005 and the soil was sampled in three distinct times, January, (starting of the rainy season), March (rainy season) and August (dry season), with 60, 120 and 270 days after the distribution of the manure, respectively at the soil depths of 0 to 20 and 20 to 40 cm and it was analyzed the physical attributes: clay dispersion in water, degree of flocculation, soil density, total porosity, soil macro and micro pores, soil resistant to penetration and stability of aggregates in water. The physical attributes of the soil were influenced by the poultry bed and swine manure applications, in greater magnitude in the different times and sampling depths. Clay dispersion content in water had decrease as the residue dosage increased. On the other hand, there was a raise in the level of flocculation and stability of the aggregates in water as the doses of manure increased. Soil density presented a negative relation with the increase of the poultry bed and the swine manure. Total porosity, soil macro and micro porosity and soil resistance to penetration were not influenced by the fertilization with the residues. In general with the increase of the doses of organic residues, the physical attributes evaluated were improved. There is potentiality for the utilization of swine manure and poultry bed in the physical recovery of soils and degraded pastures.